INTENSI KONTINUITAS PENGGUNAAN DIGITAL PAYMENT: PERAN MAHASISWA SEBAGAI WARGA KEUANGAN DIGITAL - Erlinda Sholihah; Diyah Ariyani (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2023)
This study aims to determine the factors that influence the level of continuance intention in using digital payments by students with the Expectation Confirmation Model (ECM) theory approach. The study used primary data from 100 students who use digital payments. The analysis in this study used SEM-PLS to analyze the relationship between exogenous variables and endogenous variables with the help of SmartPLS version 3. Overall, this model accounts for 54.7% of the variance in the continuity of digital payment usage intentions. An element substantially influenced by factors such as Perceived Usefulness and Satisfaction. Of these factors, Satisfaction is the most powerful predictor of continuance intention. Along with Confirmation, Perceived Usefulness also greatly affects Satisfaction. These findings will assist stakeholders in strategizing policies to offer more innovative and flexible technology products to the wider community as digital finance citizens.